Liquid chromatography-tandem mass spectrometry method for simultaneous determination of albendazole and albendazole sulfoxide in human plasma for bioequivalence studies - Rathod, Dhiraj M.; Patel, Keyur R.; Mistri, Hiren N.; Jangid, Arvind G.; Shrivastav, Pranav S.; Sanyal, Mallika (Journal of pharmaceutical analysis, 2016)
An improved high performance liquid chromatography-tandem mass spectrometry（LC-MS/MS） method has been developed for sensitive and rapid determination of albendazole（ABZ） and its active metabolite,albendazole sulfoxide（ABZSO）,in the positive ionization mode.The method utilized solid phase extraction（SPE） for sample preparation of the analytes and their deuterated internal standards（ISs） from100 μL human plasma.The chromatography was carried out on Hypurity C_（18） column using acetonitrile-2.0 mM ammonium acetate,pH 5.0（80：20,v/v） as the mobile phase.The assay exhibited a linear response over the concentration range of 0.200-50.0 ng/mL for ABZ and 3.00-600 ng/mL for ABZSO.The recoveries of the analytes and ISs ranged from 86.03%-89.66%and 89.85%-98.94%,respectively.Matrix effect,expressed as IS-normalized matrix factors,ranged from 0.985 to 1.042 for the both analytes.The method was successfully applied for two separate studies in healthy subjects using single dose of 400 mg conventional tablets and 400 mg chewable ABZ tablets,respectively.